2011
DOI: 10.1007/s10551-011-1134-0
|View full text |Cite
|
Sign up to set email alerts
|

To Do Well by Doing Good: Improving Corporate Image Through Cause-Related Marketing

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(167 citation statements)
references
References 73 publications
(96 reference statements)
5
153
1
2
Order By: Relevance
“…By engaging in social activities and reporting on CSR, firms develop the trust and goodwill of stakeholders, which can provide them with competitive advantages (Aguilera, Williams, Conley and Rupp, 2006;Money and Schepers, 2007;Gill, 2008;Kolk and Pinkse, 2010). Research suggests that CSR reporting promotes firms' image and enhances their reputation (Gray et al, 1995b;Li et al, 2010;Vanhamme, Lindgreen, Reast and van Popering, 2012) as relationships with stakeholders are based on a positive exchange of benefits (Bear, Rahman and Post, 2010).…”
Section: Corporate Governance and Csrmentioning
confidence: 99%
“…By engaging in social activities and reporting on CSR, firms develop the trust and goodwill of stakeholders, which can provide them with competitive advantages (Aguilera, Williams, Conley and Rupp, 2006;Money and Schepers, 2007;Gill, 2008;Kolk and Pinkse, 2010). Research suggests that CSR reporting promotes firms' image and enhances their reputation (Gray et al, 1995b;Li et al, 2010;Vanhamme, Lindgreen, Reast and van Popering, 2012) as relationships with stakeholders are based on a positive exchange of benefits (Bear, Rahman and Post, 2010).…”
Section: Corporate Governance and Csrmentioning
confidence: 99%
“…These analyses were carried out to ensure that extraneous variables have the same effect on employees' perceptions, motivations and satisfaction with behaviour (e.g. Vanhamme, Lindgreen, Reast, & van Popering, 2012;Kwok & Uncles, 2005) and ensured that the potential differences in individual variables between the employees belonging to the pre and post-intervention groups were not due to the influence of individual/demographic variables. These analyses also demonstrated that the two groups are "comparable in terms of these variables that are likely to be related to the dependent variable in the study" (Rubin & Babbie, 2011, p. 260).…”
Section: Characteristics Of the Pre And Post-intervention: Chi-squarementioning
confidence: 99%
“…(Stefanie Rosen Robinson, Caglar Irmak, & Jayachandran, 2012) Giving consumers a role in contribution by providing them with a choice of cause they wish to support will result in an effective campaign. (Vanhamme, Lindgreen, Reast, & van Popering, 2012) Marketers working on enhancing the corporate image should select a cause that is found to address a primary need of the people. (Lafferty & Edmondson, 2014) Cause is more important than cause categories.…”
Section: Campaign Characteristicsmentioning
confidence: 99%